2005
DOI: 10.1063/1.1990116
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of isotope effects with the nuclear-electronic orbital approach

Abstract: This paper addresses fundamental issues that arise in the application of the nuclear-electronic orbital (NEO) approach to systems with equivalent quantum nuclei. Our analysis illustrates that Hartree-Fock nuclear wave functions do not provide physically reasonable descriptions of systems comprised of equivalent low-spin fermions or equivalent bosons. The physical basis for this breakdown is that the ionic terms dominate due to the localized nature of the nuclear orbitals. Multi-configurational wave functions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 40 publications
5
72
0
Order By: Relevance
“…The MC‐DFT approach can be utilized to study NQEs. In these calculations, the exchange‐correlation functional comprises three contributions: the electronic exchange‐correlation functional, Exce, which is usually borrowed from electronic structure DFT; the nuclear exchange‐correlation, Excn, which is neglected since it has been found to be negligible and the nuclear‐electron correlation, Ecen, for which local density approximation (LDA) functionals have been proposed . Still, in some applications of APMO‐DFT, the nuclear‐electronic correlation has been neglected …”
Section: Apmo Wavefunction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MC‐DFT approach can be utilized to study NQEs. In these calculations, the exchange‐correlation functional comprises three contributions: the electronic exchange‐correlation functional, Exce, which is usually borrowed from electronic structure DFT; the nuclear exchange‐correlation, Excn, which is neglected since it has been found to be negligible and the nuclear‐electron correlation, Ecen, for which local density approximation (LDA) functionals have been proposed . Still, in some applications of APMO‐DFT, the nuclear‐electronic correlation has been neglected …”
Section: Apmo Wavefunction Methodsmentioning
confidence: 99%
“…However, it has observed that this minimal nuclear basis set overestimates the stability of symmetric molecular conformations . Hammes‐Schiffer and coworkers developed the 2 s , 2 s 2 p , and 2 s 2 p 2 d GTFs basis sets for H, D, and T . These basis sets offer a good balance between computational cost and accuracy in some simulations of isotope effects.…”
Section: Apmo Wavefunction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Starting with the HF approximation for both electrons and nuclei, 44,46,47 their current implementation allows to include the electron-nuclear correlation either with explicitly correlated Gaussians (the NEO-XCHF and NEO-XCHF2 versions 48,49 ) or using variational and perturbative post-HF methods such as nonorthogonal CI (NOCI), 50 multi-configurational self-consistent field (MCSCF), and MP2 approaches. 51 Aimed to describe large molecular aggregates, multi-component density functional theory (DFT), first proposed by Parr et al 52 in the earlier 1980s and later by Shigeta et al 53 and Kreibich and Gross, 54 has been recently included in NOMO, 55,56 NEO, 57 and MCMO 58 implementations.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to anharmonicity, the average CÀH bond is longer than the CÀD, and thus has a larger dipole moment that more effectively stabilizes the negative charge of the carboxylate anion, as (exaggeratedly) suggested in 4 H relative to 4 D. [11] Two estimates of the difference in dipole moments vary widely, 0.0086 D versus 0.0001 D. [10b,6] This is an unresolved issue, and eminent researchers continue to invoke an inductive effect to account for secondary deuterium isotope effects. [12] The focus of the current work is to test whether there is a contribution to the isotope effect on acidity due to an inductive effect. Such a contribution is generally manifested in entropy.…”
mentioning
confidence: 99%